Reinstatement of the Sikkim Himalaya species Oberonia orbicularis (Orchidaceae, Malaxideae) - Li, Yu-Ling; Tian, Huai-Zhen; Fu, Lin; Chen, Hong-Feng; Xing, Fu-Wu; Yi, Qi-Fei (Phytotaxa, 2018)
Oberonia orbicularis (Orchidaceae, Malaxideae) has been treated as the synonym of O. pachyrachis, O. obcordata and O. maxima, respectively. Our critical examination of protologues and type materials of these four names demonstrates that they are morphologically distinct from each other. We therefore reinstate the independent specific status of O. orbicularis. A detail description of this species was also provided.